2020
DOI: 10.14740/jocmr4240
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in COVID-19

Abstract: Background: As the pandemic of coronavirus disease 2019 (COV-ID-19) continues, prognostic markers are now being identified. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are easily accessible values that have been known to correlate with inflammation and prognosis in several conditions. We used the available data to identify the association of NLR and PLR with the severity of COVID-19. Methods: A literature search using EMBASE, MEDLINE, and Google Scholar for studies reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
170
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(198 citation statements)
references
References 40 publications
16
170
1
11
Order By: Relevance
“…Furthermore, in another study, a correlation between elevated PLR and the length of hospitalization day was evidenced and it has been concluded that if PLR increased more during treatment, the patient needs longer hospitalization day and had greater possibility of severe pneumonia [25]. Furthermore, Chan et al in a meta-analysis concluded that NLR and PLR can be served as independent prognostic markers of disease severity in COVID-19 [26]. Recently, NLR and PLR have been validated as prognostic factors in various disorders such as cardiac conditions, solid tumors, sepsis, pneumonia, and ARDS [26].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, in another study, a correlation between elevated PLR and the length of hospitalization day was evidenced and it has been concluded that if PLR increased more during treatment, the patient needs longer hospitalization day and had greater possibility of severe pneumonia [25]. Furthermore, Chan et al in a meta-analysis concluded that NLR and PLR can be served as independent prognostic markers of disease severity in COVID-19 [26]. Recently, NLR and PLR have been validated as prognostic factors in various disorders such as cardiac conditions, solid tumors, sepsis, pneumonia, and ARDS [26].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Chan et al in a meta-analysis concluded that NLR and PLR can be served as independent prognostic markers of disease severity in COVID-19 [26]. Recently, NLR and PLR have been validated as prognostic factors in various disorders such as cardiac conditions, solid tumors, sepsis, pneumonia, and ARDS [26]. The SII has been proposed as a prognostic indicator in the follow-up of sepsis patients (Systemic immune in ammatory index in sepsis).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NLR, a cost-effective marker can be easily calculated from peripheral blood routine tests, and may be associated with the progression and prognosis of COVID-19. There were few meta-analyses pointing out patients with severe COVID-19 had a higher NLR than those with non-severe COVID-19 [51][52][53][54]. However, none of them evaluated the predictive values of NLR on disease severity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a correlation between elevated PLR and the length of hospitalization day was evidenced and it has been concluded that if PLR increased more during treatment, the patient needs longer hospitalization day and had greater possibility of severe pneumonia [ 25 ]. Furthermore, Chan et al in a meta-analysis concluded that NLR and PLR can be served as independent prognostic markers of disease severity in COVID-19 [ 26 ]. Recently, NLR and PLR have been validated as prognostic factors in various disorders such as cardiac conditions, solid tumors, sepsis, pneumonia, and ARDS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%